Conversion Challenges: A Case Study of Converting a Post and Lintel Structure to a Precast Concrete Structure Using Building Information Modeling (BIM) - Khosakitchalert, Chavanont; Yabuki, Nobuyoshi (Nakhara : Journal of Environmental Design and Planning, 2023)
Building Information Modeling (BIM) is now a widely accepted tool in the construction industry for designing and managing construction projects. However, converting a BIM model from one type of structure to another can be challenging. This case report aims to document the problems and challenges encountered when an engineer team attempted to create a precast concrete structural BIM model from an architectural BIM model that was initially designed to use a post and lintel system. The architect worked with the engineer team, facing several challenges when changing the structural system. One of the main challenges during the conversion process was redesigning structural elements as the structural behavior of the building changed significantly. The architectural layout and design of the building had to be altered to accommodate the new structural system. Additionally, the mechanical, electrical, and plumbing (MEP) systems had to be planned for installation within the precast concrete structure. These changes required significant effort and coordination between the different teams involved in the project. In conclusion, the case study demonstrates that converting a BIM model from one type of structure to another can be a challenging task that requires significant effort, coordination, and planning. It also shows that BIM models are not just a design tool but also a powerful tool for construction management and coordination.